Exact Solutions of a (4+1)-Dimensional Boiti-Leon-Manna-Pempinelli (BLMP) Equation (Journal of Nonlinear Modeling and Analysis, 2024)
This paper focuses on constructing the exact solutions of a (4+1)-dimensional BLMP equation via the two variables $(G'/G,1/G)$-expansion method and extended generalized Riccati equation mapping method. Firstly, themain ideas of the methods are described. Then, the methods are applied tothe equation to derive the exact solutions including singular, kink (or anti-kink) and periodic solutions. Finally, the 3D plots of some exact solutionsare observed graphically and intuitively by assigning the values of unknownparameters. The results prove that the methods are powerful, enriching thediversity of forms of exact solutions.